TUMCHAITE NA2(ZR,SN)SI4O11·2H2O-A NEW MINERAL FROM CARBONATITES OF THE VUORIYARVI ALKALI-ULTRABASIC MASSIF, MURMANSK REGION, RUSSIA - Subbotin V.V.; Merlino S.; Pushcharovsky D.Yu.; Pakhomovsky Y.A.; Ferro O.; Bogdanova A.N.; Voloshin A.V.; Sorokhtina N.V.; Zubkova N.V. (My University, 2000)
Tumchaite, Na2(Zr,Sn)Si4O11·2H2O, is a new species from the Vuoriyarvi alkali-ultrabasic massif, Murmansk Region, Russia, where it occurs as colorless to white tabular monoclinic crystals associated with calcite, dolomite, a mineral of the serpentine group and pyrite in the late dolomite-calcite carbonatites. It is transparent to translucent; with vitreous luster; and perfect cleavage on (100). Mohs hardness is 4.5, Dmeas is 2.78 (2) g/cm3. Tumchaite is optically biaxial (−), with α = 1.570 (2), β = 1.588 (2), γ = 1.594 (2), 2Vmeas = 60 (5)°, and elongation positive, Y = b, c ∧ Z = 3°. Pleochroism exists, with Y = Z = colorless, X = greenish-gray. Electron microprobe analysis gave (wt%): Na2O 13.72, CaO 0.15, SiO2 52.71, TiO2 0.35, ZrO2 20.41, SnO2 5.73, HfO2 0.60, H2O (computed assuming 2H2O pfu.) 7.86, total 101.53. The X-ray study pointed to space group P21/c, a = 9.144 (4), b = 8.818 (3), c = 7.537 (3) Å, β = 113.22 (3)°, V = 558.49 Å3, Z = 2. The strongest lines of the powder diffraction pattern [d in Å (I) (hkl)] are: 8.40 (10) (100), 5.38 (9) (111), 4.00 (8) (111), 3.401 (9) (202), 2.902 (9) (211), 2.691 (9) (131). The crystal structure of tumchaite was refined to R = 0.043 for 865 Fo > 4σ(Fo). The mineral is isotypic with penkvilksite-1M. The structure is characterized by silicate sheets parallel (100), formed by alternating clockwise- and counterclockwise-growing spiral chains of corner-sharing SiO4 tetrahedra. The sheets are connected by octahedra occupied by (Zr, Sn) at 0, 1/2, 0. The Zr/Sn ratio in the octahedra is 4. Water molecules and Na cations are placed in the cavities of the polyhedral framework. The ideal crystal-chemical formula is Na2 (Zr0.8Sn0.2)[Si4O11]·2H2O. The mineral is named tumchaite for the river Tumcha near Vuoriyarvi massif.